Alegbraic expression. Simplify. please give step by step instructions

Alegbraic expression. Simplify. please give step by step instructions

Tutors, please sign in to answer this question.

You should start with Small brackets or Paranthesis (), then go for the Curly Brackets {}. then finally you should finish with Square brackets [].

Therefore first step for

3a+{b-2[(a-b)+(b-1)]}

would be opening the small brackets

3a+{b-2[a-b+b-1]}

Next -b and +b would neutralise,

so we are left with

3a+{b-2-[a-1]}

Opening the curly brackets, we have

3a+ b-2-[a-1]

then open the square brackets and solve

2a+b-1.

will be the answer.

3a+{b-2-[(a-b)+(b-1)]}

You should start with inner parenthesis.

3a+{b-2-[a-b+b-1]}=>3a+{b-2-[a-1]}=>3a+{b-2-a+1}

=>3a+{b-a-1}=>3a+b-a-1

=>2a+b-1